2013
DOI: 10.4172/2157-7439.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanospheres Functionalized by Tio2 as a Photoactive Antibacterial Agent

Abstract: In this contribution we present comparative study on synthesis, bio-characterization and antibacterial properties of mesoporous silica nanospheres modified by titanium dioxide. Mesoporous silica nanospheres functionalized by titania were studied as light activated antibacterial agents. The analysis of the antibacterial effects on E. coli ATCC 25922 shows strong enhancement during the visible and ultraviolet light irradiation in respect to the commercial catalyst and sample free from the nanomaterials. In darkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The erosion of mesoporous silica nanosphere structure modified with titanium dioxide was also observed in contact with Streptomyces cells. After 24-h incubation, mesoporous silica shell structure was degraded with simultaneous appearance of agglomerates, which clearly demonstrated that nanomaterial structure and composition could be affected by living cells [63].…”
Section: Cytotoxicitymentioning
confidence: 98%
“…The erosion of mesoporous silica nanosphere structure modified with titanium dioxide was also observed in contact with Streptomyces cells. After 24-h incubation, mesoporous silica shell structure was degraded with simultaneous appearance of agglomerates, which clearly demonstrated that nanomaterial structure and composition could be affected by living cells [63].…”
Section: Cytotoxicitymentioning
confidence: 98%
“…Mijowska and co-workers prepared MS NPs functionalized by TiO 2 using the titania precursor titanium(IV) butoxide as a photoactive antibacterial agent. [272] The antibacterial effects of the TiO 2 -containing MS on E. coli after 24 h was evaluated by CFU. The assay showed strong enhancement upon visible and ultraviolet light irradiation compared with commercial TiO 2 .…”
Section: Ms With Metal-based Npsmentioning
confidence: 99%
“…Mijowska and co‐workers prepared MS NPs functionalized by TiO 2 using the titania precursor titanium(IV) butoxide as a photoactive antibacterial agent . The antibacterial effects of the TiO 2 ‐containing MS on E. coli after 24 h was evaluated by CFU.…”
Section: Ms In Antibacterial Applicationsmentioning
confidence: 99%
“…Due to the high WRC of TiO 2 /Perlite system, the saturation of the catalyst surface with water vapor molecules could be present. Also, it has been reported that TiO 2 is highly hydrophilic and easy to supersaturate with H 2 O molecules which could contribute to its inactivation and thus, affect its performance in the production of $OH radicals (Cendrowski et al, 2013;Rodrigues-Silva et al, 2017). Also, the saturation of the catalyst surface with reduced species of CO 2 emitted from the biofilter could be present Lingampalli et al, 2017).…”
Section: Effect Of the Supporting Materials On The Photocatalytic Actimentioning
confidence: 99%